Leiomyoma of the Greater Saphenous Vein Mimicking Inguinal Lymphadenopathy. (2nd December 2013) - Dellaportas, Dionysios; Kotsis, Thomas; Carvounis, Eleni; Samanides, Lazaros
Abstract : Introduction . Leiomyoma is a benign vascular tumor affecting the greater saphenous vein rarely. Proper histopathological examination sets the diagnosis after complete and wide surgical excision along with a normal portion of the GSV. Case Presentation . A 36-year-old woman was admitted to our hospital complaining of a dull ache on her right groin for the last three months, along with a palpable mass on the mentioned area. An ultrasound (U/S) scan revealed a solid mass measuring 3 × 2  cm. After wide surgical excision, pathological examination revealed a leiomyoma of the GSV. Discussion . Benign and mostly malignant tumors arising from the GSV are reported in the literature before. Diagnostic modalities and clinical examination cannot set a correct diagnosis preoperatively due to no specific characteristics of these tumors. Possible sarcomatous behaviour has to be kept in mind when treating tumors arising from a vessel wall and wide surgical excision as negative margins should be attempted.